From BCG vaccination routes to lung and gut microbiota: avenues to tackle Mycobacterium tuberculosis infection - Silva-Angulo, Fabiola, author; Henao-Tamayo, Marcela, advisor; Weir, Tiffany, committee member; Abdo, Zaid, committee member; Izzo, Angelo, committee member (Colorado State University. Libraries, 2021)
Tuberculosis is an infectious lung disease responsible for approximately 1.4 million human deaths, world-wide every year. The causal agent of tuberculosis, Mycobacterium tuberculosis (M. tuberculosis), has been estimated to latently infect one-third of the human population. Currently, the BCG vaccine, a live attenuated strain of Mycobacterium bovis, is the only vaccine available to control the disease. Although the BCG vaccine has been the most widely administered worldwide and has been used for more than 100 years, tuberculosis dissemination remains uncontrolled and highly prevalent, especially in developing countries. Several questions about the effect that local microbiota and the administration route of BCG vaccination make on tuberculosis immunopathogenesis remain unanswered. These questions are critical for developing new approaches to control the disease. BCG vaccination is administered intradermally, however, some studies have suggested that BCG vaccination efficacy may be dependent on the administration route. Vaccination through the natural route of M. tuberculosis infection and a combination of other routes have been studied in animal models with varying results. Currently, the analysis of vaccination through the natural infection site is an attractive approach to priming innate immunity. The first study of this thesis examined the immune response induced after BCG vaccination using different routes (aerosol, subcutaneous, intravenous, and intranasal) in C57BL/6 mic and their response to pulmonary M. tuberculosis infection. The study was focused on specific markers of both CD4+ and CD8+ T cells. Our data suggested differences in the adaptive immune response based on the route of BCG vaccination and mainly elicited by CD4+ T cell immune response, with the intranasal delivery the most effective in decreasing the growth of M. tuberculosis in lungs. Another crucial question is the effect of M. tuberculosis infection and BCG vaccination on the structure, diversity, and potential function of the host lung and gut microbiota. Thus, the objective for the second study of this thesis was to characterize the effect of BCG vaccination and M. tuberculosis infection on the lung and gut micro- and mycobiota of C57BL/6 mice. Results indicated that BCG vaccination and M. tuberculosis infection in mice altered the relative lung abundance of Firmicutes and Bacteroidetes phyla compared to the control non-vaccinated, non-infected group. Lung diversity was most affected after M. tuberculosis infection. A multivariate regression approach was used to compare the profile evolution of gut and lung microbiota. More genera had modified relative abundances associated with BCG vaccination status at the gut level compared with lung. Conversely, genera with modified relative abundances associated with M. tuberculosis infection were numerous at lung level, and indicated that the local host response against infection impacted the whole microbial flora while the immune response after vaccination modified mainly the gut microbiota. This study demonstrated that parenteral vaccination with a live attenuated microorganism induced both lung and gut dysbiosis, which may play a crucial role in the immune response to M. tuberculosis infection.
Keywords: gut-lung axis; tuberculosis; microbiome; BCG vaccine